2016
DOI: 10.1364/boe.7.001175
|View full text |Cite
|
Sign up to set email alerts
|

Continuously zoom imaging probe for the multi-resolution foveated laparoscope

Abstract: In modern minimally invasive surgeries (MIS), standard laparoscopes suffer from the tradeoff between the spatial resolution and field of view (FOV). The inability of simultaneously acquiring high-resolution images for accurate operation and wide-angle overviews for situational awareness limits the efficiency and outcome of the MIS. A dual view multi-resolution foveated laparoscope (MRFL) which can simultaneously provide the surgeon with a high-resolution view as well as a wide-angle overview was proposed and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…There have only been a few attempts of exploiting focus-tunable fluid lenses for minimally invasive surgery [29][30][31]. However, their aim was to develop zoom systems and they were not intended for fluorescence imaging neither in the visible nor the NIR.…”
Section: Discussionmentioning
confidence: 99%
“…There have only been a few attempts of exploiting focus-tunable fluid lenses for minimally invasive surgery [29][30][31]. However, their aim was to develop zoom systems and they were not intended for fluorescence imaging neither in the visible nor the NIR.…”
Section: Discussionmentioning
confidence: 99%
“…The image acquired by human eye has much higher information content in the fovea region. Such a foveation concept has already been utilized in the imaging system and video processing [21,22]. In terms of VR displays, we only need to provide high resolution for the central fovea region instead of the whole field of view.…”
Section: Introductionmentioning
confidence: 99%
“…A foveated display is needed by considering panel fabrication difficulties and data transport issue [23][24][25]. Several multi-resolution foveated display designs have been proposed [22][23][24], but these designs are still relatively bulky and difficult to integrate into a compact wearable device. Moreover, such a foveated display should be able to displace high resolution region to enable gaze-contingent technique.…”
Section: Introductionmentioning
confidence: 99%
“…Various VFEs have found a broad range of applications in many areas such as 3D microscopy, endoscopy, vision correction, display and so on [5][6][7][8][9][10]. In microscopy and endoscopy, an electrically tunable lens enables flexible volume imaging at high speeds without moving specimen or objective [7][8][9]. Tremblay et al demonstrated a contact lens switchable between normal and magnified vision using the polarization property of liquid crystal [10].…”
Section: Introductionmentioning
confidence: 99%